PUSAT PELAYANAN KESEHATAN MENTAL DI BANJARBARU - A., Viska Septy Amelia; Febrita, Yuswinda (UNIVERSITAS LAMBUNG MANGKURAT, 2025)
The increasing issue of mental health in Indonesia is caused by the increasing number of people experiencing mental health problems, especially teenagers. The survey also shows that the types of mental disorders most commonly suffered by Indonesian teenagers are anxiety disorders, around 3.7% and major depressive disorders around 1.0%. The development of a complete and adequate mental health service center, especially in Banjarbaru as the capital of South Kalimantan province, is urgently needed at this time. The method that will be used in solving problems is the Architectural Psychology approach. Problems in design will be solved using the